A comprehensive kinetic and thermodynamic study of CO2 absorption in blends of monoethanolamine and potassium lysinate: Experimental and modeling. (12th October 2019) - Ramezani, Rouzbeh; Mazinani, Saeed; Di Felice, Renzo
Highlights: The density, viscosity and CO2 loading capacity of MEA + K-Lys solution were measured. A thermodynamic model was applied to model CO2 loading capacity data. Kinetics of CO2 absorption in MEA + K-Lys solution were studied. Heat of CO2 absorption in solution was estimated and compared to other absorbents. MEA + K-Lys can be used as an alternative to MEA in the CO2 capture process. Abstract: In this work, a kinetic and thermodynamic study of CO2 absorption in blends of monoethanolamine (MEA) and potassium lysinate (K-Lys) solutions was carried out at low CO2 partial pressures and temperatures (303–323 K). The CO2 loading capacity, density and viscosity of MEA + K-Lys solutions were measured. A modified Kent-Eisenberg model was applied to predict the CO2 loading capacity and also to determine the reaction equilibrium constants for the MEA + K-Lys system. The results showed that the model predictions are in excellent agreement with the experimental data. In order to study the reaction kinetics between CO2 and the MEA + K-Lys solution, the values of the reaction rate constant, the overall reaction kinetic constant, reaction order, physical solubility and CO2 diffusivity were determined. Finally, the absorption performance of the MEA + K-Lys system was compared with other common CO2 absorbents in terms of absorption heat, CO2 loading capacity and absorption rate. It was found that MEA + K-Lys has a better performance compared to other absorbents which makes it an attractive alternative to alkanolamines for CO2 capture.